Perlindungan Hukum bagi Saksi Pelaku yang Bekerjasama (Justice Collaborator) dalam Tindak Pidana Korupsi - Revi Adityansyah; Aturkian Laia (INDO PUBLISHING, 2026)
Corruption as an extraordinary and organized crime demands the role of a justice collaborator (JC) to dismantle its core networks. This instrument was initially regulated under Supreme Court Circular (SEMA) Number 4 of 2011, strengthened by Law Number 31 of 2014, and now holds operational technical grounds through Government Regulation Number 24 of 2025. Employing a legal doctrinal method with statutory and conceptual approaches, this study aims to analyze the legal standing, forms of protection, and implementation hurdles of JCs in corruption cases. The results indicate that a JC holds a dual status as both a perpetrator and a key witness. The state provides physical and psychological protection, severed case files, and rewards such as sentence reduction. However, its effectiveness remains hindered by an ambiguous